ANALYSIS OF THE USE OF BIOGRAPHICAL TEXTS IN ENGLISH LEARNING TO IMPROVE STUDENTS' WRITING SKILLS - Sri Intan Warlina; Ira Asyura (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
This study analyzes the effectiveness of using biography texts to improve the writing skills of 11th grade students at MA Malnu Pusat Menes. The methodology used is a case study with a qualitative approach involving observation, interviews and documentation as data collection techniques. The results showed that the use of biographical texts significantly improved students' writing comprehension, especially in terms of content consistency with the title (75%), language rules (65%), and spelling and punctuation (70%). Nevertheless, some students still have problems writing texts that conform to the language rules and structure of biographies. Furthermore, the use of technology in teaching, such as PowerPoint presentations, was found to help improve students' understanding. In conclusion, biography texts are an effective way to improve students' writing skills and to foster their interest and motivation to learn to write.